Wireless sensor network topology control - Zuk, Olexandr; Romanjuk, Valeriy; Sova, Oleg (Видавництво Львівської політехніки, 2010)
Topology control process for the wireless sensor network is considered. In this article the use of rule base for making decision on the search of optimum network topology is offered for the realization of different aims of network management.
Keywords: wireless sensor network; rule base; network topology